Rotterdam Oncology Documentation (RONCDOC) – a high-quality data warehouse and tissue collection for head and neck cancer - Arta Hoesseini; Emilie A. C. Dronkers; Eveline Dieleman; Maria J. De Herdt; Marjan. H. Wieringa; Marie-Louise F. van Velthuysen; Marinella P. J. Offerman; Aniel Sewnaik; Dominiek Monserez; Stijn Keereweer; Jose A. U. Hardillo; Robert Jan Baatenburg de Jong (BMC Cancer)
Abstract Background Every year, almost 900.000 people are diagnosed with head and neck cancer (HNC) worldwide. HNC contains many different subsites and a large variability in tumor biology. This often results in small and/or heterogeneous study populations. Developing overarching databases is an efficient solution to collect and analyze data of these smaller subsets of patients and to facilitate data sharing among research groups. The few existing large databases often include only basic characteristics. In addition, hospital-based cohorts that include more variables are often not collected consecutively, resulting in selection bias. Therefore, we established a hospital-based cancer registry system “Rotterdam Oncology Documentation” (RONCDOC), a complete and consecutive data warehouse and tissue collection for HNC, directly registered at the source. The primary aim of this paper is to report on our data collection protocol in order to make the RONCDOC data accessible and reusable for other researchers, and to offer a blue print to other consortia planning to establish their own data warehouse. Methods Data collected in the Netherlands Cancer Registry (NCR) of patients with HNC were obtained from the Netherlands comprehensive cancer organization (IKNL) and merged with corresponding data from the electronic patient file (EPF). The data were manually verified using the EPF, and enriched with additional variables from the EPF according to an extensive data entry protocol. Furthermore, a comprehensive validation protocol was developed to guarantee the quality of the data. Tissue microarrays (TMAs) were constructed from resection specimens of patients with primary oral squamous cell carcinoma. Conclusion With RONCDOC, we have established a consecutive and high-quality data warehouse for HNC. This paper outlines the essential steps for establishing such a data warehouse, offering a blueprint for other consortia. Trial registration This study was approved by the ethics committee of the Erasmus Medical Center (MEC-2016–751).